1992
DOI: 10.1259/0007-1285-65-779-955
|View full text |Cite
|
Sign up to set email alerts
|

Direct coronal computed tomography of the temporomandibular joint in patients with rheumatoid arthritis

Abstract: Direct coronal computed tomography (CT) of the temporomandibular joint (TMJ) was performed in 26 patients with rheumatoid arthritis (RA) and 26 control subjects. Erosions and cysts of the mandibular condyle had a significantly higher frequency in the RA group than in the control group (p < 0.05) but there was no significant difference in the incidence of other abnormalities. Bone changes were bilateral in RA. A wide range of CT abnormalities was present in patients with RA and in the control group. There are n… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

4
33
0
1

Year Published

2006
2006
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 29 publications
(38 citation statements)
references
References 13 publications
4
33
0
1
Order By: Relevance
“…The ratio of TMJ involvement in RA has ranged from 4.7 to 84 per cent in various studies, depending on the criteria used for clinical and radiological evaluation [2][3][4][5][6][7][8][9][10][11][12][13] and uncontrolled study design. [5][6][7][8][9][10][11][12] Indeed, it is difficult to compose control groups for TMD because of the features of the general population where 75 per cent of the population have symptoms and 33 per cent have signs of TMD.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The ratio of TMJ involvement in RA has ranged from 4.7 to 84 per cent in various studies, depending on the criteria used for clinical and radiological evaluation [2][3][4][5][6][7][8][9][10][11][12][13] and uncontrolled study design. [5][6][7][8][9][10][11][12] Indeed, it is difficult to compose control groups for TMD because of the features of the general population where 75 per cent of the population have symptoms and 33 per cent have signs of TMD.…”
Section: Discussionmentioning
confidence: 99%
“…[1][2][3][4][5][6] These pathologic processes might be unrelated in some patients. However, with the use of modern diagnostic criteria, such as Research Diagnostic Criteria for Temporomandibular Disorders (RDC/TMD) that allow for multiple diagnoses and specific treatment, joint and muscular pathology might be treated separately.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, it has not yet been fully elucidated whether patients with RA of the TMJ have these factors. Goupille et al 12) reported that computed tomography (CT) findings of TMJs in patients with RA included erosion of condylar and glenoid fossa, subcondral cysts, flattening of articular eminence and joint space narrowing. Kretapirom et al 13) have indicated that magnetic resonance imaging (MRI) images of RA patients with TMJ involvement showed more frequent joint effusion and synovial proliferation than temporomandibular disorder (TMD) patients.…”
Section: Introductionmentioning
confidence: 99%
“…23 Surgery can be done if ankylosis occurs along with costochondral grafting. However, orthodontic treatment is also useful in many cases like patient having anterior open bite; these types of patients can be corrected with occlusal treatment.…”
mentioning
confidence: 99%